Clinicopathological profile of gastrointestinal tuberculosis: a multinational ID-IRI study - Tanoglu, Alpaslan; Erdem, Hakan; Friedland, Jon S.; Almajid, Fahad M.; Batirel, Ayse; Kulzhanova, Sholpan; Ormeci, Necati (Springer, 2020)
Data are relatively scarce on gastro-intestinal tuberculosis (GITB). Most studies are old and from single centers, or did not include immunosuppressed patients. Thus, we aimed to determine the clinical, radiological, and laboratory profiles of GITB. We included adults with proven GITB treated between 2000 and 2018. Patients were enrolled from 21 referral centers in 8 countries (Belgium, Egypt, France, Italy, Kazakhstan, Saudi Arabia, UK, and Turkey). One hundred four patients were included. Terminal ileum (n = 46, 44.2%), small intestines except terminal ileum (n = 36, 34.6%), colon (n = 29, 27.8%), stomach (n = 6, 5.7%), and perianal (one patient) were the sites of GITB. One-third of all patients were immunosuppressed. Sixteen patients had diabetes, 8 had chronic renal failure, 5 were HIV positive, 4 had liver cirrhosis, and 3 had malignancies. Intestinal biopsy samples were cultured in 75 cases (78.1%) and TB was isolated in 65 patients (86.6%). PCR were performed to 37 (35.6%) biopsy samples and of these, 35 (94.6%) were positive. Ascites samples were cultured in 19 patients and M. tuberculosis was isolated in 11 (57.9%). Upper gastrointestinal endoscopy was performed to 40 patients (38.5%) and colonoscopy in 74 (71.1%). Surgical interventions were frequently the source of diagnostic samples (25 laparoscopy/20 laparotomy, n = 45, 43.3%). Patients were treated with standard and second-line anti-TB medications. Ultimately, 4 (3.8%) patients died and 2 (1.9%) cases relapsed. There was a high incidence of underlying immunosuppression in GITB patients. A high degree of clinical suspicion is necessary to initiate appropriate and timely diagnostic procedures; many patients are first diagnosed at surgery.
Keywords: Tuberculosis; Immune-suppression; Gastro-intestinal; Endoscopy; Treatment